The Relationship Between Cancer Type And Chemotherapy Frequency And The Quality Of Life Of Chemotherapy Patients - hendra Dwi Cahyono; Fitri Kusumasa; Awalia Nur Hasanah; Hella Meldy Tursina; Achmad Sya'id (LPPM Universitas dr. Soebandi, 2026)
Introduction: Chemotherapy is a form of cancer treatment aimed at damaging, destroying, and inhibiting the growth of cancer cells. Although effective in treating cancer, various aspects of chemotherapy, including its side effects, can affect patients' quality of life. In 2022, the prevalence of cancer in East Java was 22.2%, while in Jember Regency it was 7.8%. Purpose: To determine the strength of the relationship between cancer type and chemotherapy frequency on the quality of life of chemotherapy patients Methods: This study falls under the category of quantitative research using a cross-sectional approach. The study population consisted of 211 individuals, with a sample of 123 respondents selected using consecutive sampling. The instruments used in this study were an observation sheet and the EORTQ-30 questionnaire. Univariate analysis of frequency distribution and percentage, bivariate analysis using the Spearman Rank test, which is considered significant if the p-value ≤ 0.05. Results: From the statistical test results, it was found that there was no relationship between the type of cancer and the quality of life of chemotherapy patients, with a significance value of 0.074 and a correlation coefficient of -0.162. There was a relationship between chemotherapy frequency and quality of life in chemotherapy patients, with a significance value of 0.023 and a correlation coefficient of -0.205 Conclusions: There was no relationship between cancer type and quality of life in chemotherapy patients, but there was a relationship between chemotherapy frequency and quality of life in chemotherapy patients.